High-flame-retardant polyolefin sheath material for automobile electronic wire
By introducing cross-linking resins and modified inorganic flame retardants into the polyolefin sheath material, combined with organic flame retardants, a synergistic flame retardant effect is formed, the problem of poor heat resistance of polyolefin sheath material is solved and high resistance is achieved Fuel and heat-resistant sheathing material is suitable for automotive electronic wires and other applications in high temperature environments.
Patent Information
- Application Number
- CN202411584623.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The polyolefin sheath has poor heat resistance and cannot effectively play a protective role in high-temperature environments, which limits its use in high-temperature applications such as automotive electronics.
By introducing a promoter cross-linking resin and a modified inorganic flame retardant, combined with an organic flame retardant, a synergistic flame retardant effect is formed, and the heat resistance and flame retardant properties of the sheath are improved.
It significantly improves the heat resistance and flame retardant properties of the sheath material, can maintain good protection effect in high-temperature environments, and is suitable for high-temperature applications such as automotive electronics.
Smart Images

Figure BDA0005123990890000041 
Figure BDA0005123990890000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sheath material preparation, and in particular relates to a highly flame-retardant polyolefin sheath material for automotive electronic wires. Background Art
[0002] The base resin of existing sheath materials is generally polyolefin resin. Compared with traditional polyvinyl chloride sheath materials, polyolefin sheath materials are halogen-free and environmentally friendly when burned, which is an important direction for the environmental protection development of sheath materials. However, since polyolefin resins do not contain halogens, they cannot decompose at high temperatures to produce halogen atoms, and thus cannot capture and combine with free radicals in the combustion reaction to terminate the oxidation reaction. Therefore, the flame retardant properties of polyolefin resins are much lower than those of polyvinyl chloride. On the other hand, polyolefin resins have poor heat resistance and are easily softened and tend to be amorphous at high temperatures, which cannot play the protective role of sheath materials, limiting the application of polyolefin resins as sheath materials in high temperature environments (such as electronic wires used in automobile engine management systems).
[0003] Therefore, in the technical field of polyolefin sheath material preparation, there is an urgent need to provide a polyolefin sheath material for automotive electronic wires that is heat-resistant, aging-resistant and flame-retardant. Summary of the invention
[0004] The object of the present invention is to provide a highly flame-retardant polyolefin sheath material for automotive electronic wires.
[0005] The technical problem to be solved by the present invention is that the polyolefin sheath material has poor heat resistance and cannot be used as a sheath material in a high temperature environment.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A highly flame-retardant polyolefin sheath material for automotive electronic wires, comprising the following raw materials in parts by weight: 40-60 parts of a polyolefin base material, 20-40 parts of a cross-linking promoting resin, 18-30 parts of an organic flame retardant, 40-70 parts of a modified inorganic flame retardant, and 0.1-1 parts of a photosensitizer;
[0008] The cross-linking promoting resin is prepared by a terminal hydroxyl dendrimer and methyl acrylate through a terminal double bond reaction;
[0009] The hydroxyl-terminated dendrimer is prepared by mixing a functional dibasic ester monomer and glycerol in a molar ratio of 3:3-4 in a first organic solvent and then subjecting the mixture to a thermal reaction under the catalysis of tetrabutyl titanate;
[0010] The functional dibasic ester monomer is prepared by mixing 2,2,6,6-tetramethylpiperidinamine and methyl acrylate in a molar ratio of 1:2-4 in a second organic solvent and then subjecting the mixture to an addition reaction.
[0011] In the present invention, by introducing a cross-linking promoting resin (i.e., a double-bonded dendrimer formed by the reaction of a terminal hydroxyl dendrimer), firstly, the terminal double bond is combined with the radiation cross-linking process in the subsequent molding to play the role of a cross-linking agent; secondly, the branched structure of the dendrimer is utilized to promote the formation of an interpenetrating network in the obtained sheath material during the molding process; thirdly, the hindered amine structure in the molecular structure of the cross-linking promoter is utilized (it has the ability to capture free radicals and decompose peroxides, and can effectively reduce, inhibit or reduce the thermal oxidation and photooxidation reaction rates of the obtained sheath material), thereby improving the heat resistance of the obtained sheath material and improving the heat resistance of the polyolefin resin base material; while introducing the cross-linking promoter, an organic flame retardant and a modified inorganic flame retardant are introduced, and it is found that the cross-linking promoting resin, the organic flame retardant and the modified inorganic flame retardant can play a synergistic flame retardant role, giving the obtained sheath material high flame retardant properties.
[0012] Furthermore, the polyolefin base material is selected from one of polyethylene resin and polypropylene resin.
[0013] Furthermore, the conditions of the terminal double bond reaction are as follows: the terminal hydroxyl dendrimer and methyl acrylate are reacted in a first organic solvent under the catalysis of tetrabutyl titanate at 140-160° C. with stirring for 3-12 hours;
[0014] In the terminal double bond reaction, the transesterification reaction between the amino group in the terminal hydroxyl dendrimer and the ester group in methyl acrylate is utilized at a temperature of 140-160°C.
[0015] Further, the functional dibasic ester monomer and glycerol are thermally reacted in a first organic solvent, comprising:
[0016] Functional dibasic ester monomer and propylene glycol are mixed with tetrabutyl titanate in a first organic solvent at a molar ratio of 3:3-4, heated to a first reaction stage temperature, stirred and reacted for a first predetermined time, heated to a second stage reaction temperature, stirred and reacted for a second predetermined time, and then post-treated to obtain a terminal hydroxyl dendrimer.
[0017] In the thermal reaction of the functional dibasic ester monomer and propylene glycol in the first organic solvent, the ester exchange hyperbranching reaction between the dibasic ester group in the functional dibasic ester monomer and the dibasic terminal alcohol hydroxyl group in propylene glycol is utilized, and the molar ratio of the functional dibasic ester monomer and propylene glycol is controlled (3:3-4) to form a terminal hydroxyl dendrimer.
[0018] Furthermore, the temperature of the first reaction stage is 90-110° C., the first predetermined time is 1.5-3 h, and the temperature of the second reaction stage is 120-150° C., the second predetermined time is 1.5-3 h.
[0019] In the thermal reaction of the functional dibasic ester monomer and propylene glycol in the first organic solvent, the present invention further controls the thermal reaction process, and improves the number average molecular weight of the obtained terminal hydroxyl dendrimer by controlling the reaction temperature and reaction time in two stages, and reduces the discrete degree of the number average molecular weight of the obtained terminal hydroxyl dendrimer.
[0020] Furthermore, under the above two-stage thermal reaction process with reaction temperature and reaction time, the number average molecular weight of the obtained hydroxyl-terminated dendrimer is 20,000-30,000.
[0021] Furthermore, the first organic solvent is one of benzene, toluene, N,N-dimethylformamide and N,N-dimethylacetamide.
[0022] Furthermore, the addition reaction temperature is 0-40°C, and the reaction time is 4-24h.
[0023] In the addition reaction, the addition reaction between 1 mol amino group in 1 mol 2,2,6,6-tetramethylpiperidinamine and 2 mol double bonds in 2 mol methyl acrylate is utilized to form a functional dibasic ester monomer.
[0024] Furthermore, the molecular structure of the functional dibasic ester monomer is shown below.
[0025]
[0026] Furthermore, the second organic solvent is one of methanol, dichloromethane, benzene, toluene, N,N-dimethylformamide and N,N-dimethylacetamide.
[0027] Furthermore, the modified inorganic flame retardant is white carbon black modified by a silane coupling agent.
[0028] Preferably, the silica modified by the silane coupling agent is silica modified by a double-bond silane coupling agent.
[0029] Furthermore, the organic flame retardant is melamine cyanurate.
[0030] Furthermore, the highly flame-retardant polyolefin sheath material for automotive electronic wires further comprises 1-5 parts by weight of processing auxiliary materials, and the processing auxiliary materials are selected from one of lubricants.
[0031] Beneficial effects of the present invention:
[0032] The invention not only improves the heat resistance of the obtained sheath material, but also gives the obtained sheath material high flame retardancy by promoting the introduction of cross-linked resin and modified inorganic flame retardant. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The double-bond silane coupling agent-modified silica in the following embodiments is all KH570-modified silica, wherein the modification method is the surface grafting modification well known in the technical field, utilizing the hydrolyzed high-activity silanol bonds in the silane coupling agent to hydrolyze the hydroxyl bonds on the surface of the silica to form a graft, thereby obtaining silica with the surface grafted silane coupling agent. The surface grafting modification process in the present invention is a well-known process in the technical field and will not be described in detail herein.
[0035] Example 1
[0036] Facilitates the preparation of cross-linked resins:
[0037] A1. In an ice water bath, add 0.25 mol methyl acrylate to a mixture of 0.1 mol 2,2,6,6-tetramethylpiperidinamine and 60 mL methanol under stirring. After the addition is complete, heat to 20°C, continue stirring and reacting for 12 hours, heat to 60-70°C and evaporate to recover the solvent, continue to heat to 75-85°C and evaporate to recover excess methyl acrylate to obtain a functional dibasic ester monomer;
[0038] A2, 0.1 mol functional dibasic ester monomer, 0.3 mol propylene glycol, 0.5 g tetrabutyl titanate and 150 mL N, N-dimethylacetamide were mixed evenly, heated to 100° C., stirred and reacted for 1.5 hours, heated to 120° C., stirred and reacted for 3 hours, methanol was continuously evaporated during the reaction, and after the reaction was completed, the reaction was dried under reduced pressure to obtain a hydroxyl-terminated dendrimer;
[0039] A3. The hydroxyl-terminated dendrimer obtained in step A2 is mixed with 100 mL of N,N-dimethylacetamide, heated until the hydroxyl-terminated dendrimer is dissolved, stirred evenly, and then an excess of methyl acrylate (in this embodiment, the amount of methyl acrylate added is equal to the amount of propylene glycol added) and 0.8 g of tetrabutyl titanate are added, heated to 140° C. under reflux condensation, stirred for reaction for 12 h, then rotary evaporated at 75-85° C. to recover excess methyl acrylate, rotary evaporated at 60-70° C. to remove methanol, and after rotary drying, washed and dried to obtain a cross-linking-promoting resin.
[0040] Example 2
[0041] Facilitates the preparation of cross-linked resins:
[0042] A1. In an ice water bath, add 0.4 mol methyl acrylate to a mixture of 0.1 mol 2,2,6,6-tetramethylpiperidinamine and 60 mL methanol under stirring. After the addition is complete, heat to 30°C, continue stirring and reacting for 12 hours, heat to 60-70°C and evaporate to recover the solvent, continue to heat to 75-85°C and evaporate to recover excess methyl acrylate to obtain a functional dibasic ester monomer;
[0043] A2, 0.1 mol functional dibasic ester monomer, 0.4 mol propylene glycol, 0.6 g tetrabutyl titanate and 150 mL N, N-dimethylacetamide were mixed evenly, heated to 90°C, stirred and reacted for 3 hours, heated to 150°C, and continued to stir and react for 1.5 hours. During the reaction, activated carbon was set at the tail gas treatment position to absorb the evaporated methanol. After the reaction was completed, the reaction was dried under reduced pressure to obtain a hydroxyl-terminated dendrimer;
[0044] A3. Mix the hydroxyl-terminated dendrimer obtained in step A2 with 100 mL of N,N-dimethylacetamide, heat until the hydroxyl-terminated dendrimer is dissolved, stir evenly, add an excess of methyl acrylate (in this embodiment, the amount of methyl acrylate added is equal to the amount of propylene glycol added) and 1 g of tetrabutyl titanate, heat to 160° C. under reflux condensation, stir and react for 3 h, then rotary evaporate at 75-85° C. to recover excess methyl acrylate, rotary evaporate methanol at 60-70° C., spin dry, wash and dry to obtain a cross-linking-promoting resin.
[0045] Example 3
[0046] Preparation of highly flame-retardant polyolefin sheath materials for automotive electronic wires:
[0047] 1. Prepare the following raw materials in parts by weight: 60 parts of low-density polyethylene, 20 parts of the cross-linking promoting resin prepared in Example 1, 18 parts of an organic flame retardant (MCA), 70 parts of a modified inorganic flame retardant (white carbon black modified with a double-bond silane coupling agent, with a white carbon black particle size of 400-500 nm), 15 parts of a photosensitizer (photoinitiator 819), 0.1 parts of a lubricant (polyethylene wax), and 1 part of a polyethylene wax.
[0048] 2. Add the above raw materials in parts by weight into a twin-screw extruder, extrude and granulate to obtain a sheath material.
[0049] Example 4
[0050] Preparation of highly flame-retardant polyolefin sheath materials for automotive electronic wires:
[0051] 1. Prepare the following raw materials in parts by weight: 50 parts of low-density polyethylene, 30 parts of the cross-linking promoting resin prepared in Example 2, 24 parts of organic flame retardant (MCA), 60 parts of modified inorganic flame retardant (white carbon black modified by double bond silane coupling agent, with a white carbon black particle size of 400-500nm), 0.5 parts of photosensitizer (photoinitiator 819), and 2 parts of lubricant (polyethylene wax);
[0052] 2. Add the above raw materials in parts by weight into a twin-screw extruder, extrude and granulate to obtain a sheath material.
[0053] Example 5
[0054] Preparation of highly flame-retardant polyolefin sheath materials for automotive electronic wires:
[0055] 1. Prepare the following raw materials in parts by weight: 40 parts of low-density polyethylene, 40 parts of the cross-linking promoting resin prepared in Example 1, 30 parts of organic flame retardant (MCA), 45 parts of modified inorganic flame retardant (white carbon black modified by double bond silane coupling agent, with a white carbon black particle size of 400-500nm), 1 part of photosensitizer (photoinitiator 819), and 5 parts of lubricant (polyethylene wax);
[0056] 2. Add the above raw materials in parts by weight into a twin-screw extruder, extrude and granulate to obtain a sheath material.
[0057] Comparative Example 1
[0058] Preparation of sheath material:
[0059] Compared with Example 3, an equal amount of the cross-linking promoting resin in the raw material is replaced with the hydroxyl-terminated dendrimer prepared in step A2 of Example, and the rest is the same.
[0060] Comparative Example 2
[0061] Preparation of sheath material:
[0062] Compared with Example 3, the cross-linking promoting resin in the raw material is deleted, and the rest is the same.
[0063] Comparative Example 3
[0064] Preparation of sheath material:
[0065] Compared with Example 3, the modified inorganic flame retardant in the raw materials is deleted, and the rest is the same.
[0066] Comparative Example 4
[0067] Preparation of sheath material:
[0068] Compared with Example 3, the organic flame retardant in the raw material is deleted, and the rest is the same.
[0069] Comparative Example 5
[0070] Preparation of sheath material:
[0071] Compared with Example 3, the cross-linking promoting resin, organic flame retardant and modified inorganic flame retardant in the raw materials are deleted, and the rest are the same.
[0072] After the sheath materials obtained in Examples 3-5 and Comparative Examples 1-5 were irradiated and formed, physical properties were tested, and the results were shown in Table 1. Among them, the UV aging resistance was tested according to GB / T 16422.3, and the test time was 168h, and then the tensile strength was tested, and the decrease rate of the tensile strength was calculated. The heat aging resistance was tested according to GB / T7141, and the tensile strength was tested after the heat aging test was completed, and the decrease rate of the tensile strength was calculated.
[0073] Table 1
[0074]
[0075] From the data in Table 1, it can be seen that the sheath materials obtained in Examples 3-5 have good heat resistance, heat aging resistance, UV aging resistance and flame retardancy.
[0076] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. Highly flame-retardant polyolefin sheath material for automotive electronic wires, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of polyolefin base material, 20-40 parts of promoting cross-linking resin, 18-30 parts of organic flame retardant, 40-70 parts of modified inorganic flame retardant, and 0.1-1 parts of photosensitizer; The cross-linking promoting resin is prepared by a terminal hydroxyl dendrimer and methyl acrylate through a terminal double bond reaction; The hydroxyl-terminated dendrimer is prepared by mixing a functional dibasic ester monomer and glycerol in a molar ratio of 3:3-4 in a first organic solvent and then subjecting the mixture to a thermal reaction under the catalysis of tetrabutyl titanate; The functional dibasic ester monomer is prepared by mixing 2,2,6,6-tetramethylpiperidinamine and methyl acrylate in a molar ratio of 1:2-4 in a second organic solvent and then subjecting the mixture to an addition reaction.
2. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The polyolefin base material is selected from one of polyethylene resin and polypropylene resin.
3. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The conditions of the terminal double bond reaction are as follows: the terminal hydroxyl dendrimer and methyl acrylate are reacted in a first organic solvent under the catalysis of tetrabutyl titanate at 140-160° C. with stirring for 3-12 hours.
4. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The thermal reaction of the functional dibasic ester monomer and glycerol comprises: Functional dibasic ester monomer and propylene glycol are mixed with tetrabutyl titanate in a first organic solvent at a molar ratio of 3:3-4, heated to a first reaction stage temperature, stirred and reacted for a first predetermined time, heated to a second stage reaction temperature, stirred and reacted for a second predetermined time, and then post-treated to obtain a terminal hydroxyl dendrimer.
5. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 4, characterized in that: The temperature of the first reaction stage is 90-110° C., the first predetermined time is 1.5-3 hours, the temperature of the second reaction stage is 120-150° C., and the second predetermined time is 1.5-3 hours.
6. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The first organic solvent is one of benzene, toluene, N,N-dimethylformamide and N,N-dimethylacetamide.
7. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The addition reaction temperature is 0-40°C, and the reaction time is 4-24h.
8. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The second organic solvent is one of methanol, dichloromethane, benzene, toluene, N,N-dimethylformamide and N,N-dimethylacetamide.
9. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The modified inorganic flame retardant is white carbon black modified by a silane coupling agent, and the organic flame retardant is melamine cyanurate.
10. The highly flame-retardant polyolefin sheath material for automotive electronic wire according to claim 1, characterized in that: The invention also comprises 1-5 parts by weight of processing auxiliary materials, wherein the processing auxiliary materials are selected from a lubricant.
Citation Information
Patent Citations
Preparation method of acid and alkali resistant ultraviolet-curing adhesive film resin for glass base material
CN104086742A
Polyethylene resin cable sheath material
CN105860223A
Method for preparing halogen-free low-smoke flame-retardant cross-linked polyolefin sheath material for photovoltaic cables
CN106317604A
High-flame-retardant polyolefin sheath material for automobile electronic wire
CN115850845A
Anti-aging photovoltaic cable material and preparation method thereof
CN117487287A